Edwin G. Crocker letter to Peter C. Petersen and Gladys Black regarding sighting of a Snowy Owl, January 29, 1980 - Crocker, Edwin G.et al (1980)
Field notes contributed by Edwin G. Crocker in a letter to Peter C. Petersen and Gladys Black, regarding sighting of a Snowy Owl on January 25, 1980. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of winter 1979-1980. Epson - sheet feed/flatbed